Language, Religion, and Identity Negotiation in Indonesian Islamic Boarding Schools: A Sociolinguistic Ethnography - Indrasanti, Lutfi; Wita, Fitri Rahma (Jurnal Tahuri, 2023)
This study aims to examine how language is used and negotiated by students (santri) in shaping their religious and social identities at Pondok Pesantren Modern Terpadu Al-Kautsar Al-Akbar, West Sumatra. The pesantren represents a complex multilingual social space where Arabic, Indonesian, and Minangkabau are alternately used across religious, academic, and everyday domains. Adopting a sociolinguistic ethnographic approach, the research employed participant observation, natural interaction recordings, and in-depth interviews with students, teachers, and administrators. Critical discourse analysis was applied to interpret how linguistic practices reflect ideologies, authority, and identity negotiations within the pesantren setting. The findings reveal that Arabic functions as a symbol of piety and religious authority, Indonesian serves as a medium of rationality and academic communication, while Minangkabau affirms intimacy and local identity. Code-switching and code-mixing among these languages are not random but reflect strategic positioning within the intersecting demands of religiosity, institutional discipline, and social solidarity. The study introduces the concept of linguistic piety negotiation, referring to the balancing process between religious devotion and national belonging through language use. This research contributes to sociolinguistic studies of identity by uncovering the interplay between religious and national language ideologies in modern Islamic education, an area rarely explored in Indonesia, and offers insights for understanding the ideological and unifying roles of language in multilingual Muslim communities.